2020
DOI: 10.1002/gps.5381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of pimavanserin in the treatment of agitation and aggression in patients with Alzheimer's disease psychosis: A post hoc analysis

Abstract: Funding information ACADIA Pharmaceuticals Inc Objectives: Patients with Alzheimer's disease psychosis (ADP) commonly experience concomitant agitation and aggression. We investigated whether a reduction in ADP following pimavanserin treatment conferred a reduction in associated agitation and aggression. Methods: ACP-103-019 was a 12-week, randomized, double-blind, placebocontrolled study that evaluated the efficacy of pimavanserin (34 mg) in reducing psychotic symptoms in patients with ADP. The primary endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Pimavanserin is approved for the treatment of psychosis in Parkinson’s disease and appears not to produce extrapyramidal effects (Cummings et al ., 2014). This agent reduced agitation in persons with AD and psychosis if the psychosis responded to treatment (Ballard et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Pimavanserin is approved for the treatment of psychosis in Parkinson’s disease and appears not to produce extrapyramidal effects (Cummings et al ., 2014). This agent reduced agitation in persons with AD and psychosis if the psychosis responded to treatment (Ballard et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search identified 10 studies that met our inclusion criteria. Five studies included comparisons of pimavanserin with atypical antipsychotics [47] , [48] , [49] , [50] , [51] , two were comparisons between pimavanserin and a control group of untreated patients [53] , [54] , one was a comparison of pimavanserin users to pimavanserin nonusers [52] , and two were pimavanserin OLEs [57] , [63] . Overall, the two Medicare database studies were likely the most rigorous and comprehensive, and both demonstrated comparable or lower all-cause MRs among new users of pimavanserin versus other atypical antipsychotics [47] , [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Nabilone may improve agitation; however, more studies are needed to confirm these results ( Herrmann et al, 2019 ). On the other hand, pimavanserin may improve both agitation and aggression in patients with AD ( Ballard et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%